Willingness to Participate in Mammography Screening: A Randomized Controlled Questionnaire Study of Responses to Two Patient Information Leaflets With Different Factual Content - Gummersbach, Elisabeth (Dtsch Arztebl Int, 2015)
BACKGROUND: From 2010 onward, a new leaflet about mammography screening for breast cancer, more informative than the preceding version, has been sent to women in Germany aged 50 to 69 with the invitation to undergo screening. The purpose of this study was to determine the effect of different informational content on the decision whether or not to be screened. METHODS: In a randomized and blinded design, 792 women aged 48 to 49 were sent either the old or the new leaflet. Questionnaires were sent together with the leaflets in order to assess the following: willingness to undergo mammography screening, knowledge, decisional confidence, personal experiences of breast cancer, and demographic data. RESULTS: 370 (46.7%) of the questionnaires were returned, and 353 were evaluable. The two groups did not differ significantly in their willingness to be screened: 81.5% (95% confidence interval [CI] 75.8%–87.2%) versus 88.6% (95% CI 83.9%–91.3%, p = 0.060). A post-hoc analysis showed that women who reported having had personal experience of breast cancer (18.7%) were more willing to be screened if they were given the new leaflet, rather than the old one (interaction p = 0.014). The two groups did not differ in their knowledge about screening (p = 0.260). Women who received the old leaflet reported a higher decisional confidence (p = 0.017). The most commonly mentioned factors affecting the decision were experience of breast cancer in relatives and close acquaintances (26.5% of mentions) and a doctor’s recommendation (48.2%). Leaflets (3.6%) and all other factors played only a secondary role. CONCLUSION: The greater or lesser informativeness of the leaflet affected neither the participants’ knowledge of mammography screening nor their willingness to undergo it. The leaflet was not seen as an aid to decision-making. The best way to assure an informed decision about screening may be for the patient to discuss the matter personally with a qualified professional.